Two Types of Fuzzy Logic Controllers for the Fuel and Oxygen Flows of the Solid Oxide Fuel Cell - Roqiya Saada (University of Msila, 2025)
Solid Oxide Fuel Cells (SOFCs) are highly efficient and environmentally friendly energy systems; however, their nonlinear dynamics and sensitivity to input variations present significant control challenges. One of the most critical aspects of SOFC operation is output voltage regulation, which directly impacts system stability, efficiency, and seamless integration with external loads or power grids. To ensure a stable output voltage under varying operating conditions-such as load fluctuations or changes in fuel composition-advanced control strategies are necessary. Effective regulation requires precise management of key variables, particularly fuel and oxygen flow rates, which directly influence electrochemical reactions and, consequently, the SOFC’s output voltage. This study conducts a comparative analysis of three distinct control strategies for SOFC voltage regulation: PID Controller A widely used method favored for its simplicity, but often insufficient when dealing with nonlinearities and uncertainties. Type-1 Fuzzy Logic Controller A rule-based control approach capable of handling moderate system nonlinearities effectively. Type-2 Fuzzy Logic Controller An advanced version of T1-FLC that integrates uncertainty into fuzzy sets, providing enhanced robustness in dynamic environments.
Keywords: Solid Oxide Fuel Cell; voltage Regulation; Nonlinear Dynamics; PID Controller